Consumption of energy drinks among Turkish University students and its health hazards - Borlu, Arda (Pak J Med Sci, 2019)
OBJECTIVE: To determine the awareness, consumption patterns of energy drinks (ED) and health hazards among students at a Turkish University. METHODS: This cross-sectional descriptive study was conducted by questionnaire method between in 2017 among Erciyes University students. Total 1257 students from the Faculties of Medicine, Communication and Physical Education and Sports College participated in the study. Pearson chi-square test, binary logistic regressions were used for statistical analysis. p <0.05 values were considered significant. RESULTS: Students who tried at least once and consumed regularly ED were 52.5% and 15.7% respectively. Consuming regularly and trying ED were more common among students who were studying at Physical Education and Sports High school, male, smoking, alcohol consumer, doing regular physical activity. Mean age of students to start drinking ED was 15.1 years. Most common reason for ED consumption was; staying awake. Alcohol mixed energy drinks consumption rate was 37.6% among regular ED consumers. Most declared harmful effect was palpitation. CONCLUSION: ED consumption among Erciyes University students was widespread. Students should be informed about EDs’ hazards for health. Legal regulations regarding production, marketing and advertising of EDs must be reconsidered.